2022
DOI: 10.1101/2022.03.29.486301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accounting for cis-regulatory constraint prioritizes genes likely to affect species-specific traits

Abstract: Measuring differences in allele specific gene expression in hybrids between two different species is a powerful way to detect cis-regulatory changes underlying adaptation. However, these studies frequently identify thousands of differentially expressed genes. This makes it difficult to differentiate candidate genes most likely to explain interspecies phenotypic differences from genes whose expression levels diverge with little evolutionary constraint. Here we outline a simple strategy that leverages population… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Turning our attention to regulatory mechanisms, the use of fused cell lines allowed us to assess the relative contribution of cis and trans changes to regulatory evolution – an approach that has not been feasible in primates until recently (Agoglia et al, 2021; Gokhman et al, 2021; Starr et al, 2022). We found that cis changes are common and can impact any number of cell types, as expected given the potential for spatial and temporal specificity of cis elements.…”
Section: Discussionmentioning
confidence: 99%
“…Turning our attention to regulatory mechanisms, the use of fused cell lines allowed us to assess the relative contribution of cis and trans changes to regulatory evolution – an approach that has not been feasible in primates until recently (Agoglia et al, 2021; Gokhman et al, 2021; Starr et al, 2022). We found that cis changes are common and can impact any number of cell types, as expected given the potential for spatial and temporal specificity of cis elements.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, using allele-specific expression data from human-chimpanzee hybrid cortical spheroids, Starr et al (2022) recently found that expression of CUX1 from the human allele is lower than expression from the chimpanzee allele. These results suggest that reduced TR gene expression has played a role in human brain evolution.…”
Section: Evidence Of Reduced Tr Gene Expression During Human Evolutionmentioning
confidence: 99%
“…Since in hybrids both alleles experience the same environment, including trans-acting regulators, this approach is particularly well-suited for identifying cis-regulatory changes between species. Recently, this method was used to detect reduced CUX1 expression in humans (Starr et al, 2022), and we expect future studies using interspecies hybrids to reveal further examples of human-specific TR gene downregulation.…”
Section: Predictions and Suggestions For Future Workmentioning
confidence: 99%
See 1 more Smart Citation